1991
DOI: 10.1007/bf01395602
|View full text |Cite
|
Sign up to set email alerts
|

Heliothis virescens: Response characteristics of receptor neurons in Sensilla Trichodea type 1 and type 2

Abstract: Partial electroantennograms (EAGs) and single cell recordings fromHeliothis virescens males have demonstrated the presence of pheromones receptor neurons in sensilla trichodea type 2 as well as in type 1. This is supported by cobalt tracing experiments, showing that primary axons from the distal flagellum, containing only s. trichodea type 2, project into the macrogiomerulus complex in the male antennal lobes. Four types of finely tuned pheromone receptor neurons were found in males, whereas in females the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
55
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 22 publications
2
55
0
Order By: Relevance
“…2), but gave only a very faint band in PCR experiments with preparations from female antennae. Electrophysiological recordings from individual olfactory cells in male antennae of Heliothis have demonstrated that components of the female sex pheromone are perceived by means of specific sensory cells in sensilla trichodea types 1 and 2, whereas host-plant odors are perceived by means of sensory cells of other sensilla types (20,21). The observation that the novel receptor types HR13-HR16 were expressed in cells that could be confined to long sensilla trichodea supports the view that they are candidate pheromone receptors.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…2), but gave only a very faint band in PCR experiments with preparations from female antennae. Electrophysiological recordings from individual olfactory cells in male antennae of Heliothis have demonstrated that components of the female sex pheromone are perceived by means of specific sensory cells in sensilla trichodea types 1 and 2, whereas host-plant odors are perceived by means of sensory cells of other sensilla types (20,21). The observation that the novel receptor types HR13-HR16 were expressed in cells that could be confined to long sensilla trichodea supports the view that they are candidate pheromone receptors.…”
Section: Discussionmentioning
confidence: 76%
“…In many moth species, the antennae are sexually divergent; usually, only male antennae contain sex-pheromoneresponsive cells, which may comprise as many as 50% of all chemosensory antennal cells (29). However, in H. virescens also, females might possess a few sensory neurons responding to pheromones (20). Interestingly, HR13 was found to be highly expressed in male antennae (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations